2021
DOI: 10.1039/d1tc04729a
|View full text |Cite
|
Sign up to set email alerts
|

A new insight into the ZIF-67 based triboelectric nanogenerator for self-powered robot object recognition

Abstract: Harvesting mechanical energy from surroundings can be a promising power source for micro/nano-devices. The triboelectric nanogenerator (TENG) works in the principle of triboelectrification and electrostatic induction. So far, the metals...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
38
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 42 publications
(43 citation statements)
references
References 49 publications
5
38
0
Order By: Relevance
“…The results indicated that the smaller particle size could lead to better output performance. For comparison, we listed the several important literature studies in this area in Table S1. ,, From the table, it can be concluded that our work reached a relatively high level in this area.…”
Section: Resultsmentioning
confidence: 99%
“…The results indicated that the smaller particle size could lead to better output performance. For comparison, we listed the several important literature studies in this area in Table S1. ,, From the table, it can be concluded that our work reached a relatively high level in this area.…”
Section: Resultsmentioning
confidence: 99%
“…The ZIF-67 maintains its original morphology after being attached with electrodes. [219] Shaukat et al prepared MOF-5, which is having high chemical, thermal stability having rod-like morphology and tunable porosity shows outstanding properties in the fabricated TENG. Whereas, the MOF-5 acts as tribo-positive layer and polytetrafluoroethylene (PTFE) acts as a tribo-negative layer in TENG and achieved a maximum output Voc is 484 V while Isc achieved 40 μA with an efficient power of 3,174 μW.…”
Section: Mof Based Materialsmentioning
confidence: 99%
“…TENG provides a high level of versatility because of its ease of manufacture, four operating modes, diverse material selection, and increased output. 23 They have several potential uses, including powering small electronic devices like sensors and actuators and self-powered systems like wearable gadgets. 24 TENGs are also being investigated as a potential source of power for the Internet of Things (IoT) devices and usage in distant regions where traditional power sources are unavailable.…”
Section: Introductionmentioning
confidence: 99%
“…When the materials are separated, the electrons flow back to their original materials, generating an electric current. TENG provides a high level of versatility because of its ease of manufacture, four operating modes, diverse material selection, and increased output . They have several potential uses, including powering small electronic devices like sensors and actuators and self-powered systems like wearable gadgets .…”
Section: Introductionmentioning
confidence: 99%